2005
DOI: 10.1074/jbc.m410276200
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Gene Encoding a 1,2-Diacylglycerol-sn-acetyl-CoA Acetyltransferase from Developing Seeds of Euonymus alatus

Abstract: 1,2-Diacyl-3-acetyl-sn-glycerols (ac-TAG) are unusual triacylglycerols that constitute the major storage lipid in the seeds of Euonymus alatus (Burning Bush). These acTAGs have long-chain acyl groups esterified at both the sn-1 and sn-2 positions of glycerol. Cell-free extracts of developing seeds of E. alatus contain both long-chain acyl-CoA and acetyl-CoA sn-1,2-diacylglycerol acyltransferase (DGAT) activity. We have isolated a gene from developing seeds of Euonymus alatus that shows a very high sequence sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…DGAT enzyme activity was measured by in vitro assay (Zou et al, 1999) containing 100 mM Tris-HCl, pH 8.0, 400 mM diacylglycerol (delivered from a 40 mM stock in methanol), 20 mM [1-14 C]acyl-CoA (specific activity, 20,000 cpm/mmol; prepared enzymatically as described by Rajasekharan et al [1993]), and 25 mg of yeast microsomal membrane protein in a total volume of 100 mL. The mixture was incubated at 308C for 1 h and then extracted twice with 400 mL of hexane:isopropanol (3:2, v/v) (Milcamps et al, 2005). The upper hexane phases were pooled, dried under N 2 , redissolved in a small volume of chloroform containing 200 mg of carrier trilinolein, and chromatographed on silica gel TLC plates using n-hexane:diethyl ether:acetic acid (80:20:1, v/v) as the mobile phase.…”
Section: Yeast Extract Preparation and In Vitro Dgat Enzyme Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…DGAT enzyme activity was measured by in vitro assay (Zou et al, 1999) containing 100 mM Tris-HCl, pH 8.0, 400 mM diacylglycerol (delivered from a 40 mM stock in methanol), 20 mM [1-14 C]acyl-CoA (specific activity, 20,000 cpm/mmol; prepared enzymatically as described by Rajasekharan et al [1993]), and 25 mg of yeast microsomal membrane protein in a total volume of 100 mL. The mixture was incubated at 308C for 1 h and then extracted twice with 400 mL of hexane:isopropanol (3:2, v/v) (Milcamps et al, 2005). The upper hexane phases were pooled, dried under N 2 , redissolved in a small volume of chloroform containing 200 mg of carrier trilinolein, and chromatographed on silica gel TLC plates using n-hexane:diethyl ether:acetic acid (80:20:1, v/v) as the mobile phase.…”
Section: Yeast Extract Preparation and In Vitro Dgat Enzyme Assaymentioning
confidence: 99%
“…The type 1 class of DGAT enzymes (DGAT1) was discovered first in mouse based on homology with mammalian acyl-CoA:cholesterol acyltransferase genes (Cases et al, 1998); subsequently, other DGAT1 genes were identified and characterized in several plant species (Hobbs et al, 1999;Routaboul et al, 1999;Zou et al, 1999;Bouvier-Navé et al, 2000;Nykiforuk et al, 2002;He et al, 2004b;Milcamps et al, 2005). For instance, the Arabidopsis thaliana DGAT1 gene has been shown to contribute significantly to seed TAG biosynthesis, both by overexpression (Jako et al, 2001) and through mutational downregulation studies (Katavic et al, 1995;Routaboul et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Microsomal membranes were prepared by a published method (Milcamps et al, 2005) with minor modifications. Yeast cultures expressing DGAT variants were grown in 100-mL volumes to early stationary phase, harvested, and resuspended in 4 mL of 20 mM Tris-HCl, pH 8, 10 mM MgCl 2 , 1 mM EDTA, 5% glycerol, 1 mM dithiothreitol, and 300 mM (NH 4 ) 2 SO 4 .…”
Section: Microsomal Membrane Preparations and Dgat Activitymentioning
confidence: 99%
“…DGAT1 has been characterized from several plant species (Routaboul et al 1999;Zou et al 1999;Milcamps et al 2005). Seed-specific overexpression of DGAT1 results in an increase in the seed size and oil content (Jako et al 2001;Taylor et al 2009), but disruption of DGAT1 led to a reduced oil content in seeds (Routaboul et al 1999;Zou et al 1999).…”
Section: Introductionmentioning
confidence: 99%